2021
DOI: 10.1016/j.bbi.2020.09.014
|View full text |Cite
|
Sign up to set email alerts
|

IgA natural antibodies are produced following T-cell independent B-cell activation following stroke

Abstract: Up to 30% of stroke patients experience cognitive decline within one year of their stroke. There are currently no FDA-approved drugs that can prevent post-stroke cognitive decline, in part due to a poor understanding of the mechanisms involved. We have previously demonstrated that a B-lymphocyte response to stroke, marked by IgA + cells, can cause delayed cognitive dysfunction in mice and that a similar adaptive immune response occurs in the brains of some human stroke patients that suffer from vascular dement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…3C) . These perturbations in innate and adaptive immunity demonstrate that chronic inflammation persists in infarcts for at least 7 weeks after stroke, as we have shown previously (Chung et al, 2018; Doyle et al, 2015; Zbesko et al, 2020).…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…3C) . These perturbations in innate and adaptive immunity demonstrate that chronic inflammation persists in infarcts for at least 7 weeks after stroke, as we have shown previously (Chung et al, 2018; Doyle et al, 2015; Zbesko et al, 2020).…”
Section: Resultssupporting
confidence: 85%
“…Similar to atherosclerotic plaques, chronic stroke infarcts contain foamy macrophages, lipid droplets, and intracellular and extracellular cholesterol crystals (Chung et al, 2018). We have also shown that the development of these pathologies coincides with the recruitment and infiltration of adaptive immune cells (Doyle et al, 2015;Zbesko et al, 2020). Importantly, in atherogenesis, the formation of foamy macrophages, caused by dysregulated lipid metabolic processes, leads to the recruitment of adaptive immune cells and the production of cytokines and degradative enzymes.…”
Section: Discussion (1500 Words Maximum Including Citations)mentioning
confidence: 85%
See 3 more Smart Citations